Underground Press of Social Democratic Organizations in Šiauliai in 1904–1914 - Petreikis, Tomas (Knygotyra, 2021)
This article deals with propaganda activities, such as publishing proclamations (20 publications), revolutionary songs (1), and underground periodicals (1), by local organizations of the Bund, LSDDP, LSDP and RSDDP in Šiauliai in 1904–1914. Political changes in Russia in 1904–1907 created favorable conditions for social democratic organizations to actively carry out propaganda activities, but the intensity at which they were carried out was not uniform across Lithuania. The proletarian profile of Šiauliai and the particularly active activity of the LSDP allowed to mobilize propagandists in a short time, to prepare the necessary proclamations on the spot, and to provide the necessary press equipment. During the years of the revolution (1905–1907), Šiauliai had to emerge as the second center of the social democratic movement in Lithuania. After the defeat of the revolution in Russia, due to the increased persecution of social democratic forces, the underground organizations failed to mobilize their press capacity or develop more active propaganda events; therefore, the political parties even had to suspend the activities of local organizations in Šiauliai. The integration of social democratic youth into the social democratic organizations of Šiauliai took place in c. 1912 and gave hope for a stronger revival of propaganda. The resumption of activities ceased in the first years of the First World War. The large-scale underground press developed in underground conditions expressed the expectations of the local population, reflected the involvement of parties in the formation of political views of the urban population, and was a counterweight to official information. Therefore, its assessment is inseparable from the realities of the political context of that time.